Hewan Model Pada Penelitian Penemuan Kandidat Antimalaria Sebagai Upaya Percepatan Pengendalian Malaria - Novita, Risqa (Program Studi Pendidikan Geografi Universitas Pattimura, 2023)
Malaria is a disease that is very old from a century ago but is still found today and is the highest cause of death in the world, especially in children. Indonesia is also still not free from malaria. The protozoan parasites that cause malaria in Indonesia are Plasmodium falciparum and Plasmodium vivax, but currently the prevention of malaria in Indonesia is coupled with the presence of Simian Malaria which is zoonotic and is caused by Plasmodium knowlesi. Malaria prevention requires research in experimental animals to determine effective prevention, to know the pathogenesis of the disease, and the nature of the protozoa, and to be able to determine the appropriate antimalarial. This paper is a literature review that reviews animal models of malaria. The results of a literature search indicated that two animal models of different orders were needed to be able to determine the appropriate antimalarial and to be able to determine the nature of the protozoa in different animal models